The philosophical foundations of the judicial reasoning method in the mental structure of the administrative judge - Mohammad Hussein Al-Majali (International Journal of Law Research and Studies, 2026)
This research addresses the philosophical framework of judicial reasoning within the cognitive structure of the administrative judge, conceptualizing it as a complex intellectual process that extends beyond the literal application of legal rules toward the construction of a judicial discourse grounded in interpretation, justification, and the reconfiguration of facts in light of the principle of legality. The study is based on a central problem concerning the philosophical foundations governing the formation of administrative judicial reasoning, and the extent to which formal logic intersects with purposive and functional interpretative reasoning in shaping judicial conviction.The research adopts an analytical–philosophical methodology aimed at deconstructing the cognitive structure of the judge’s reasoning process by linking classical Aristotelian deductive logic with modern developments in legal philosophy that emphasize the role of context, interpretation, and legislative purpose. It further examines the judicial mindset as an evolving cognitive system in which legal norms interact with judicial experience and factual assessment, resulting in a reasoned and coherent judicial decision.The study concludes that judicial reasoning in administrative adjudication is no longer a mechanical application of legal rules, but rather a constructive process that reconfigures the relationship between legal norms and factual reality within a balance between legality and administrative justice. It further highlights legal philosophy as the intellectual foundation that explains the evolution of judicial justification techniques and delineates the boundaries of judicial discretion.
Keywords: Administrative Judicial Reasoning; Philosophy of Administrative Law; Administrative Judicial Mindset